Experience with Basiliximab (Simulect ®) in a particular Kidney Transplant Unity - Matuck , Tereza; Morgado , Luciano; Alvarenga , Maria de Fátima; Borela , Álvaro; Pires , Ana Cláudia; Reis , Marília Drumond; Graciano , Miguel Luis; Trindade , Jayne Almeida da; Carvalho, Deise Monteiro de (Brazilian Journal of Transplantation, 2005)
Objective: To evaluate if Basiliximab, a chimeric monoclonal antibody that blocks interleukin-2 receptor, is safe and effective in preventing acute rejection in high risk renal transplant recipients that were received a kidney allograft between august/1999 and august/2002. Methods: We analyzed 75 high-risk renal transplants. All patients received 20mg of Basiliximab on day zero and on day four post-transplant except children under 40kg that received 10 mg on both days. Sex, age, race, cause of end stage renal dysfunction, type of donor, dialysis vintage, immunosuppression regimen, side effects, incidence of rejection, incidence of infections, graft and patient survival were analyzed. Results: Infection rate was 70,6% and the most frequent site was urinary tract (38,7%). The time of appearance was 2,27 ± 1,8 months. Rejection episodes were diagnosed in 17,6% of the patients, with good answer to steroid therapy. The only important side effect occurred in a child: seizure. One patient lost the graft due to technical problem and two died with good graft function. The patient survival rate at 6 months a was 97,6%. Conclusion: Basiliximab use was safe and effective in the prevention of acute rejection in high-risk renal transplant recipients.